Perbandingan Lama Hari Rawat Terapi Non Spesialis dan Spesialis Keperawatan pada Pasien Gangguan Jiwa - Sumirat, Asep Rusman Iriana; Akemat, Akemat; Made, Made; Khrisna, Khrisna; Rahmi, Rahmi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to compare the length of stay of mental disorder patients who receive non-specialist and specialist therapy at RSJMM. The method used is quantitative with a comparative method. The results showed that the length of stay of specialist therapy patients was 16.03 ± 2.945 days, with a median of 17 days, the shortest length of stay was 3 days, and the most extended length of stay was 21 days. The length of stay of non-specialist patients was 16.98 ± 2.81 days, with a median of 17 days; the shortest length of stay was 6 days, and the most extended length of stay was 28 days. The Mann-Whitney test (p of 0.015 <0.05) showed a significant difference in the average length of stay between patients who received specialist and non-specialist nursing services. In conclusion, specialist nurses better understand patient needs and design appropriate interventions, resulting in a fast discharge of an average of 0.95 days. Keywords: Mental Disorders, Mental Health Nursing, Length of Stay, Specialist Therapy.